Characterization of Aspercetin, a Platelet Aggregating Component from the Venom of the Snake Bothrops asper which Induces Thrombocytopenia and Potentiates Metalloproteinase-induced Hemorrhage - Rucavado, Alexandra; Soto, Mónica; Kamiguti, Aura S.; Theakston, David G.; Fox, Jay W.; Escalante, Teresa; Gutiérrez, José María (Thrombosis and Haemostasis, 2001)
Thrombocytopenia occurs in a number of patients bitten by Bothrops asper, a species responsible for the majority of snakebites in Central America and southern Mexico. In this work we describe the isolation of a new platelet-aggregating protein, named aspercetin, from the venom of B. asper, which induces thrombocytopenia in mice. Isolation was carried out by a combination of ion-exchange chromatography on DEAE-Sepharose and affinity chromatography on Affi-Gel Blue. Aspercetin is a disulfide-linked heterodimer, with a pI of 4.5 and a molecular mass of 29,759 Da, detemined by MALDI-ESI mass spectrometry. N-terminal sequence shows homology with a number of venom proteins which belong to the C-type lectin family. Aspercetin has functional similarities with botrocetin, from B. jararaca venom, since it induces platelet aggregation only in the presence of plasma or purified von Willebrand factor. Aspercetin-mediated platelet aggregation results from the interaction of von Willebrand factor with platelet receptor GPIb. Aspercetin lacks anticoagulant effect and does not agglutinate erythrocytes, in contrast with other representatives of the C-type lectin family isolated from snake venoms. Moreover, aspercetin is not lethal, nor does it induce myonecrosis, hemorrhage and edema. When injected intravenously or intramuscularly in mice it induces a rapid, dose-dependent drop in platelet counts and prolongs the bleeding time, suggesting that it may play a role in the thrombocytopenia that develops in a number of B. asper envenomations. Moreover, mice injected intravenously with aspercetin and then receiving an intradermal injection of B. asper hemorrhagic metalloproteinase BaP1 develop a larger hemorrhagic lesion than mice receiving only BaP1. This suggests that aspercetin, by reducing platelet numbers, may contribute to the hemorrhagic effect characteristic of B. asper envenomations.
Keywords: Platelet aggregation; Bothrops asper venom; aspercetin; C-type lectin; hemorrhage; thrombocytopenia